Potret Identitas Marginal dalam Sastra Kontemporer: Pelabelan terhadap Anak PKI dalam Novel Namaku Alam Karya Leila S. Chudori - Moh. Ruddin; Moh. Tabarok; Santi Oktaviani; Ari Ambarwati (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study aims to describe the labeling process in Leila S. Chudori's novel Namaku Alam (My Name is Alam) related to the main character's status as a child of the Indonesian Communist Party (PKI), deviance, and its impact, using Howard S. Becker's labeling theory. The method used is qualitative with a sociology of literary texts (soteksas) approach. Data were obtained through library research and in-depth reading, with the researcher as the main instrument. The unit of analysis includes linguistic and contextual elements that represent the labeling process. The analysis was carried out through the stages of label identification, narrative interpretation, application of Becker's theory (stigma construction, articulation of deviation, and identity response), and connection with the social context. The results show that the character Alam received stigmatic labels such as